The classification of regular and defected low voltage XLPE cable by using polarization and depolarization current method - Singhasivanon, J.; Manop, C.; Pattanadech, N.; Jirasuwankul, N. (My University, 2017)
Electric cable is an important part of utility power and distribution system. In order to keep the system operation safely and reliable, acceptance testing for cable is necessary not only inservice but also manufacturing process. This paper proposes a novel testing technique which is able to classify the difference between normal and defective low voltage XLPE cable, namely polarization and depolarization current technique (PDC). In this study, PDC testing of low voltage XLPE cable was performed comparatively among five different cases: cable contaminated with a piece of paper, case 2 : cable contaminated with a piece of plastic, case 3 : cable contaminated with grease, case 4 : cable contaminated with a piece of copper, and case 5 : Eccentric conductor cable. With environmental control of the testing process, the test results show the polarization current of the defective contaminated cable with copper is higher than that of the regular one, whereas it is lower than that of the defective one with paper, plastic and grease. It is also found that there was indistinctive of PDC in case of copper contaminated and eccentric conductor cable.
Keywords: Cable contaminate; Defected cable; Dielectric; Polarization and depolarization current; Xlpe cable